Answer:
x = 1
y = 2
z = 3
Explanation:
Given:
2x + 3y - z = 5
or
z = 2x + 3y - 5 ............(1)
4x - y - z = -1 ..........(2)
x + 4y + z = 12 ...........(3)
substituting 1 in 2, we get
4x - y - ( 2x + 3y - 5 ) = -1
or
4x - y - 2x - 3y + 5 = -1
2x - 4y + 6 = 0
or
x - 2y + 3 = 0
or
x = 2y - 3
substituting x in equation 1 , we get
z = 2( 2y - 3 ) + 3y - 5
or
z = 4y - 6 + 3y - 5
z = 7y - 11
substituting x and z in 3 we get
( 2y - 3 ) + 4y + ( 7y - 11 ) = 12
or
-14 + 13y = 12
or
y = 2
substituting y in z = 7y - 11, we get
z = 7 × 2 - 11
or
z = 3
substituting y in x = 2y - 3
we get
x = 2 × 2 - 3
or
x = 1
thus,
x = 1
y = 2
z = 3